Understanding barriers and facilitators of inter-organizational dynamics in addressing substance use disorder among pregnant and parenting women - Sugy Choi; Elizabeth Knopf; Megan A. O’Grady; Ivy Van Domselaar; Jessica Ortiz; Carla King; Charles J. Neighbors; Thomas D’Aunno (PLoS ONE, 2025)
Background Pregnant and parenting women with substance use disorders (SUDs) face complex and overlapping challenges, including substance use, legal issues, housing instability, and trauma. Effective interorganizational collaboration is critical but often hindered by fragmented care and resource limitations. This study explores the key barriers and facilitators that impact collaborative efforts among healthcare providers, government agencies, and community organizations in addressing SUD among pregnant and parenting women. Methods This qualitative study was conducted in New York State between April 2022 and April 2023. The study focused on organizations that provide services to pregnant and parenting women with SUDs, including government agencies, SUD treatment centers, healthcare settings, and community-based care organizations. Semi-structured, one-on-one interviews were conducted with staff to explore how their organizations coordinate care. Thematic analysis was used to identify patterns related to interorganizational collaboration. Primary data were collected through interviews with 30 staff members across multiple stakeholder groups: child welfare services (n = 8), criminal legal agencies (n = 5), health agencies (n = 3), healthcare service settings (n = 4), SUD treatment programs (n = 6), and community-based organizations (n = 4). Interviews lasted approximately one hour and focused on organizational roles, referral processes, and coordination efforts in serving the target population. Results Collaborative care was primarily facilitated through referral networks, case management teams, and the presence of embedded healthcare professionals. However, these systems were frequently limited by fragmented communication, stigmatizing attitudes, and insufficient resources. Organizational facilitators included co-located healthcare staff within child welfare services and formalized partnerships across sectors. Key barriers included staffing shortages, burnout, and misalignment of organizational goals. At the individual level, collaboration often depended on informal relationships and staff-driven initiatives, though interdisciplinary knowledge gaps remained a significant challenge. Conclusions Improving service coordination for pregnant and parenting women with SUDs will require stronger organizational infrastructure, investment in cross-sector communication strategies, and deliberate efforts to address stigma. Future research should explore models that support sustained, formalized interagency partnerships to enhance care integration.